2012
DOI: 10.1186/1744-8069-8-77
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetyl-Cysteine Causes Analgesia by Reinforcing the Endogenous Activation of Type-2 Metabotropic Glutamate Receptors

Abstract: BackgroundPharmacological activation of type-2 metabotropic glutamate receptors (mGlu2 receptors) causes analgesia in experimental models of inflammatory and neuropathic pain. Presynaptic mGlu2 receptors are activated by the glutamate released from astrocytes by means of the cystine/glutamate antiporter (System xc- or Sxc-). We examined the analgesic activity of the Sxc- activator, N-acetyl-cysteine (NAC), in mice developing inflammatory or neuropathic pain.ResultsA single injection of NAC (100 mg/kg, i.p.) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 54 publications
2
61
0
Order By: Relevance
“…Some components of the vesicular docking mechanism are seen at the level of the somatic membrane within the ganglion (Figure S1). Alternatively, channels and transporters through which non-vesicular release of glutamate occurs are also present, including the cystine-glutamate antiporter [46], gap junctions (connexin 43) [23], the P2X7 channel [28], [47], or reverse transport through GLAST or GLT1 [21], [43]. Although we did not see glutamate immuno-staining in SGCs it is possible that this due to the limited sensitivity of immunocytochemistry.…”
Section: Discussionmentioning
confidence: 81%
“…Some components of the vesicular docking mechanism are seen at the level of the somatic membrane within the ganglion (Figure S1). Alternatively, channels and transporters through which non-vesicular release of glutamate occurs are also present, including the cystine-glutamate antiporter [46], gap junctions (connexin 43) [23], the P2X7 channel [28], [47], or reverse transport through GLAST or GLT1 [21], [43]. Although we did not see glutamate immuno-staining in SGCs it is possible that this due to the limited sensitivity of immunocytochemistry.…”
Section: Discussionmentioning
confidence: 81%
“…In addition to the direct inhibition of the activation of MMP-9 in DRGs as revealed by Colorimetric quantitative detection in this study, previous studies indicated that NAC may alleviate neuropathic pain and inflammatory pain through reducing nitric oxide metabolites [42], scavenging reactive oxygen species (ROS) [43], and enhancing endogenous activation of type-2 metabotropic glutamate receptors (mGluR) in spinal cord [44]. The gelatin lytic activity and expression of MMP-9 could also be abolished indirectly by NAC via its ROS scavenging effect [45].…”
Section: Discussionmentioning
confidence: 99%
“…; Sigma Chemical Co., St Louis, MO), an inhibitor of system x c − (Bernabucci et al 2012; Gout et al 2001; Sontheimer and Bridges 2012), was dissolved in isotonic saline and brought to a pH between 6.0 and 8.0 using NaOH. Testing commenced two hours following acute sulfasalazine treatment as described below.…”
Section: Methodsmentioning
confidence: 99%